2000
DOI: 10.1103/physreve.62.6282
|View full text |Cite
|
Sign up to set email alerts
|

Surmounting oscillating barriers: Path-integral approach for weak noise

Abstract: We consider the thermally activated escape of an overdamped Brownian particle over a potential barrier in the presence of periodic driving. A time-dependent path-integral formalism is developed which allows us to derive asymptotically exact weak-noise expressions for both the instantaneous and the time-averaged escape rate. Our results comprise a conceptually different, systematic treatment of the rate prefactor multiplying the exponentially leading Arrhenius factor. Moreover, an estimate for the deviations at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 48 publications
8
79
0
Order By: Relevance
“…The results in (21) and (22) are also consistent with Figure 1, which suggests that r(0, η) increases as a concave function of η. The queueing counterpart is such that the load is one, and hence the reneging is necessary to alleviate the system.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The results in (21) and (22) are also consistent with Figure 1, which suggests that r(0, η) increases as a concave function of η. The queueing counterpart is such that the load is one, and hence the reneging is necessary to alleviate the system.…”
supporting
confidence: 79%
“…As discussed in Section 5 the transition to oscillatory behavior occurs when R ≈ γ 2 /4 and then we can approximate D R−1 (γ) by Airy functions, with the leading term given in (87). Thus with R = γ 2 /4 − (γ/2) 2/3 δ and γ → ∞ the minimal root corresponds to the maximal root of Ai(δ) = 0, which occurs at δ = a 0 , leading to (22).…”
Section: Nowmentioning
confidence: 99%
“…This is similar to the POs used by Lehmann et al [63][64][65] for the case of thermal activation with additive periodic driving. Note that this TS trajectory Γ ‡ is an exact solution to the equations of motion.…”
Section: B Anharmonic Barriersmentioning
confidence: 55%
“…For thermally induced reactions, Lehmann, Reimann, and Hänggi [63][64][65] have shown that in the overdamped (large-γ) regime, when a chemical reaction is forced by a periodic field the reaction rate is determined in part by the geometry of periodic trajectories in the purely deterministic phase space. This work was later extended to cases with different scaling behaviors between the strength of thermal activation and the strength of the external field.…”
Section: Characterizing Noisy Reactions With the Noise-free Geometrymentioning
confidence: 99%
“…The subject of our present paper is one of the simplest and experimentally most natural such non-equilibrium descendants of Kramers' original escape problem [17], namely the thermally activated escape of a Brownian particle over a potential barrier in the presence of periodic driving which modulates both the corresponding potential well region and the activation barrier. While most previous attempts have been restricted to weak [25,26,27], slow [28,29], or fast [25,28,30] driving, we have addressed in recent analytical explorations [31,32] by means of a path-integral technique the most challenging intermediate regime of moderately strong and moderately fast driving for a one-dimensional, overdamped escape problem. Closely related to our recent works are the subsequent appealing efforts in Ref.…”
Section: Introductionmentioning
confidence: 99%